2009
DOI: 10.1111/j.1365-2788.2009.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment severity is associated with health status among older persons with intellectual disability and cerebral palsy*

Abstract: With the exception of dysphagia, impairment in ADLs and walking capabilities, and not CP diagnosis alone, accounted for disparities in specific diseases. Although the diagnosis of CP may be correlated with functional impairment, it alone may play a minor role in determining health trajectories in older persons with conjoint ID and CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 43 publications
0
57
0
2
Order By: Relevance
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Uma vez que a fonoterapia não modificou favoravelmente o desempenho da biomecânica da deglutição nem o nível de ingestão oral, sugere-se que as complicações, sejam estas de origem orgânica ou intelectual encontradas nesta população, sejam discutidas como marcadores deste controle de eficácia 27,28 .…”
Section: Discussionunclassified
“…Generally speaking, physical health issues appeared to be unrelated to the type of CP; however, difficulties in motor activity and ADLs may have contributed to some of these health concerns. In some studies, gender impacted the prevalence or risk for certain comorbid physical issues, such as fragility fractures from osteopenia in women (Henderson et al, 2009). Additionally, other social determinants of health, such as ethnicity or socioeconomic status (SES), may also impact the prevalence of comorbid physical issues in individuals with CP, although these were not specifically examined in the reviewed literature.…”
Section: Chronic Physical Health Issues In Adults With Cpmentioning
confidence: 98%
“…Only one of the studies reviewed (Henderson et al, 2009) investigated physical health issues in a sample of adults with CP and ID. Although Turk, Geremski, Rosenbaum, and Weber (1997) indicated that the sample included individuals with CP and ID; the authors failed to present findings specific to individuals with CP and ID.…”
Section: Chronic Physical Health Issues In Adults With Cpmentioning
confidence: 98%
See 1 more Smart Citation